Kristal hemoglobin pada darah dan bercak darah yang terpapar beberapa shampo cuci sepeda motor menggunakan tes Teichmann dan tes Takayama - M. Fajrul Ihsan; Enikarmila Asni; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstain is one of important evidence in a forensic laboratoryexamination, especially in cases o violence or crime. Attempted in removingevidence of bloodstain with cleaning agents such as motorcycle wash shampoo isa challenge in the investigation. The purpose of this study is to observe crystalhemoglobin in blood and bloodstains exposed with motorcycle wash shampoousing Teichmann and Takayama test. This study is experimental research. Theblood slides and bloodstains slides were washed using 2 kind of motorcycle washshampoo as many as one to three times. In the study, 28 (100%) slides havepositive result whether with Teichmann or Takayama test. It can be concludedthat hemoglobin crystal are still can be found in blood and bloodstain expand willsome motorcycle wash shampoo using Teichmann and Takayama test.Keywords: bloodstain, hemoglobin crystal, motorcycle wash shampoo,Teichmann, Takayama